Enhancement on optical properties and radiation shielding performance of new formulation zinc modified boro-tellurite glasses - Sani, Aliyu; Mohd Zaid, Mohd Hafiz; Matori, Khamirul Amin; Abdul Karim, Muhammad Khalis; Wei, Loh Zhi (Elsevier Ltd, 2025)
The main goal of this research is to determine the fundamental characteristics of xZnO − 30B2O3−(70-x)TeO2 glass system that can be used as radiation shielding. Ultrasonic analysis and UV–Vis results show Urbach energy ranges from 1.071 to 0.737 S-1, whereas the direct and indirect optical band gaps increase between 3.194 and 3.270 and 2.22 to 2.64 eV, respectively. The density of the glasses varies between 4.25 and 4.04 g/cm3. As the ZnO concentration increases, all elastic moduli decrease as well as microhardness from 5.63 to 3.92 GPa and Poisson's ratio from 0.26 to 0.24 based on the results from ultrasonic measurement. The refractive index of a glass changes from 1.98 to 2.02, their molar volume decreases from 32.77 to 28.91 cm3/mol, and molar weight decreases from 132.61 to 116.96 g/mol, whereas oxygen molar volume ranges from 12.1 to 9.73, and the oxygen packing density changes from 2.3 to 2.1 mol/cm3. Electronegativity, Optical Polarizability, and Basicity ranging from 0.86 to 0.87, 2.73 to 2.71, and 1.27 to 1.26, respectively. All the radiation factors for the robust glass system were calculated using the Phy-X/PSD programming.